Structural modeling and biochemical characterization of recombinant KPN_02809, a zinc-dependent metalloprotease from Klebsiella pneumoniae MGH 78578 - Wong, Mun Teng; Choi, Sy Bing; Kuan, Chee Sian; Chua, Siang Ling; Chang, Chiat Han; Mohd Yahaya, Normi; See Too, Wei Cun; A. Wahab, Habibah; Few, Ling Ling (MDPI, 2012)
Klebsiella pneumoniae is a Gram-negative, cylindrical rod shaped opportunistic pathogen that is found in the environment as well as existing as a normal flora in mammalian mucosal surfaces such as the mouth, skin, and intestines. Clinically it is the most important member of the family of Enterobacteriaceae that causes neonatal sepsis and nosocomial infections. In this work, a combination of protein sequence analysis, structural modeling and molecular docking simulation approaches were employed to provide an understanding of the possible functions and characteristics of a hypothetical protein (KPN_02809) from K. pneumoniae MGH 78578. The computational analyses showed that this protein was a metalloprotease with zinc binding motif, HEXXH. To verify this result, a ypfJ gene which encodes for this hypothetical protein was cloned from K. pneumoniae MGH 78578 and the protein was overexpressed in Escherichia coli BL21 (DE3). The purified protein was about 32 kDa and showed maximum protease activity at 30 °C and pH 8.0. The enzyme activity was inhibited by metalloprotease inhibitors such as EDTA, 1,10-phenanthroline and reducing agent, 1,4-dithiothreitol (DTT). Each molecule of KPN_02809 protein was also shown to bind one zinc ion. Hence, for the first time, we experimentally confirmed that KPN_02809 is an active enzyme with zinc metalloprotease activity.